Deep Source Regions for Back‐Arc Volcanism in the Patagonian Slab Window Imaged by Finite Frequency P and SH Body Wave Tomography - Ben Mansour, Walid (2025)
The subduction of the Chile Ridge beneath South America beginning 12–16 Myr ago opened a gap in the subducting slab beneath southern Patagonia, which migrated northward and is located today at 46°S. Geodynamic processes associated with the slab window are poorly understood. Here we apply finite‐frequency P and SH body wave tomography to seismic data from several temporary arrays as well as regional stations to image seismic heterogeneities down to 650 km depth. The results show strong low velocity anomalies extending to 400 km depth beneath recent back‐arc volcanism between 46°S and 48°S, suggesting a link to thermal upwelling in the upper mantle. The southern edge of the Nazca slab extends aseismically down to at least 350 km. We also image low upper mantle seismic velocities beneath the Patagonia icefields, suggesting low viscosity modulates the patterns of uplift and horizontal deformation observed by GNSS.